FAKTOR YANG MEMPENGARUHI MOTIVASI MAHASISWA DALAM PENYELESAIAN SKRIPSI ( STUDI TERHADAP MAHASISWA BIMBINGAN DAN KONSELING ANGKATAN 2006-2007 STKIP PGRI SUMATERA BARAT). - Hamidi, Pirman; Kasih, Fitria; Yusnetti, Yusnetti (Bimbingan dan Konseling, 2013)
Based on the observation that researchers do the students STKIP PGRIÂ  Sumatera Barat, especially student guidance and counseling that many students who have not completed a thesis which should have finished working on the thesis, there is still a student class of 2006 and 2007 who have not completed the thesis. The problem in this study is what are the factors that influence student motivation in the completion of the thesis. This study aimed to describe: (1) Intrinsic factors that influence student motivation in the completion of thesis (2) extrinsic factors that influence student motivation in the completion of the thesis. This research is a descriptive study sought to describe a situation for what it is. The population in this study were all students of guidance and counseling 2006-2007 forces numbering 25 students. Techniques used in sampling is sampling in which the total amount of the entire population sampled in the study. So the total sample of 25 people. The instrument used in this study was a questionnaire. While the data used for the analysis of the percentage formula. Results of this study found that (1) the intrinsic factors that influence student motivation in the completion of the thesis is in many categories, as many as 22 students or 88% of the students expressed a lot of factors that affect motivation. (2) Extrinsic factors that influence student motivation in the completion of the thesis is in many categories, as many as 20 students or 80% of the students expressed a lot of factors that affect motivation.Â